Glucose-6-phosphate dehydrogenase deficiency near-patient tests for tafenoquine or primaquine use with Plasmodium vivax malaria - Praveen Weeratunga (2022)
Objectives: This is a protocol for a Cochrane Review (diagnostic). The objectives are as follows:. To assess the diagnostic accuracy of near-patient tests for G6PD deficiency in people undergoing treatment or prophylaxis with primaquine or tafenoquine for malaria; or in people at risk of or susceptible to malaria. Secondary objectives To investigate sources of heterogeneity, namely the following. Age: adults versus children Sex: male versus female Reported prevalence of G6PD (high versus low) Malaria endemicity (endemic versus non-endemic) Geographic location (continent of residence; that is, Africa, Asia, or other continent) Reference standard used (adjusted male median, median G6PD, laboratory standard) Type of blood used (venous versus capillary) To compare the accuracy of each type of test.